Evaluation of Tangible Fixed Assets Acquisition in the Corporate Income Tax Planning Framework in Relation to Tax Efficiency at PT. Es Bali - N K P Handayani; W H Utthavi; N W D Ayuni (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
Assets are one of the most important parts of a company that must be managed properly. In the procurement of fixed assets, the company should consider the most favorable financing alternatives either in cash, credit or leasing. This research was conducted to know the application of tax planning, which purchasing alternative among of cash, credit and finance lease that gives the highest tax saving for PT. Es Bali. The data in this study is secondary data in the form of asset data purchased by the company, interest rate, interest rate to be used as discout factor, and down payment of lease paid by the company. The data collection procedure used in this research is in the form of documentation technique. The analysis by the authors in this study using quantitative data analysis techniques and data analysis techniques descriptive comperative. The results show that financial lease method provides the largest tax savings compared with other methods. Financial lease method gives tax savings of Rp. 116,978,703 for the nominal value and Rp. 236,445,409 for the present value compared to credit financing. Meanwhile, when compared with the cash method, leasing gives a tax savings of Rp. 319,927,006 for the nominal value and Rp. 397,521,943 for the present value. This is because the financial lease has a deductible expense tax deductions more than the method of cash and bank credit.